'Through Trade Unionism you felt a belonging – you belonged': Collectivism and the Self-Representation of Building Workers in Stevenage New Town. Issue 3 (December 2016) - McGuire, Charlie
Abstract : Building workers in Britain have often been portrayed as individualistic and independent – a fragmented and atomised sector of workers who are largely uninterested or incapable of being involved in a common struggle to improve conditions generally. However, the oral histories of a group of workers employed in the building industry in Stevenage during the post-war decades suggest a very different reality. For these workers, collectivism, solidarity, sacrifice, and struggle were the key themes of their experience on construction sites during the 1950s–1970s period. A strong commitment to trade unionism was central to this, and was also a key resource through which they constructed their self-identities.